DETERMINATION OF ASSET REVALUATION - Evi, Tiolina (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to analyze the factors that influence asset revaluation decisions. The sample in this study are all industrial companies on the Indonesia Stock Exchange from 2012 to 2016 except the banking industry with a purposive sampling technique. The method of analysis in this study uses partial least square. The results showed that investment opportunities represented by the book value of the asset market did not affect asset revaluation. Debt equity ratios, debt asset ratios, current ratios, and fast ratios do not affect asset revaluation. Request a quote, and total assets do not affect asset revaluation. However, only the ownership structure represented by foreign ownership can have a positive effect on asset revaluation. Keywords: Investment Opportunities, Leverage, Asymmetric Information, Ownership Structure, Liquidity And Firm Size.